Halogen-free vapor phase epitaxy for high-rate growth of GaN bulk crystals. (29th March 2017) - Nakamura, Daisuke; Kimura, Taishi; Horibuchi, Kayo
Abstract: Here, we propose a halogen-free vapor phase epitaxy (HF-VPE) technique to grow bulk GaN single crystals. This technique employs the simplest reaction for GaN synthesis (reaction of Ga vapor with NH3 ) and can potentially achieve a high growth rate, a prolonged growth duration, a high crystal quality, and a low cost. The analyses of thick HF-VPE-GaN layers grown under optimized growth conditions revealed that high-quality crystals, both in terms of dislocation density and impurity concentration, are obtained at high growth rates of over 100 µm/h.